Exploring the role and mechanisms of the PMA gene in Aspergillus fumigatus - Chengrui Tan; Shaojie Jiang; Hongli Zhai; Qingwen Hu; Chenxi Liu; Yi Sun; Lujuan Gao (Mycology)
In the realm of aspergillosis, a critical concern for immunocompromised patients facing Aspergillus fumigatus, effective management hinges on understanding fungal growth, stress resistance, and response to antifungal treatments. Our study investigates the crucial role of fungal plasma membrane proton ATPase (PMA) in nutrient absorption, intertwined with growth and antifungal susceptibility. We employed a high-throughput knockout method to create the PMA gene knockout mutant, ΔAfu-PMA1, in A. fumigatus, alongside a complementation strain. Antifungal susceptibility to triazoles was assessed by micro-dilution method and E-test, revealing decreased sensitivity to voriconazole in ΔAfu-PMA1. Comparative analysis demonstrated significant growth differences, with wild-type strain surpassing ΔAfu-PMA1 by 3.2-fold. Under oxidative stress and heightened osmotic pressure, ΔAfu-PMA1 showed notable growth defects. Loss of PMA led to increased ergosterol and decreased ATP content, alongside pH changes in the culture medium. Transcriptome sequencing unveiled revealed a reduced expression of genes associated with ribosome function, the MAPK pathway, endoplasmic reticulum, and the transport and metabolism of fats, sugars, and proteins in ΔAfu-PMA1, highlighting PMA’s regulatory role in growth and adaptation. These findings emphasise PMA as a potential target for future antifungal drugs, offering hope in combating aspergillosis.